100: Non-Dairy Milk Consumption is Associated with Lower Serum 25-Hydroxyvitamin D in Early Childhood. Issue 6 (1st June 2014) - Lee, GJ; Birken, CS; Parkin, PC; Lebovic, G; Chen, Y; L'abbe, MR; Maguire, JL
Abstract: BACKGROUND: Vitamin D fortification of cow's milk is the main dietary source of vitamin D in early childhood. The consumption of non-dairy milk, such as plant-based milk beverages and goat's milk is increasing. Vitamin D fortification of non-dairy milk is voluntary in North America. We hypothesize that the consumption of non-dairy milk may be associated with lower 25-hydroxyvitamin D in early childhood. OBJECTIVES: For our primary objective, we aimed to determine if there is an association between daily volume of non-dairy milk consumption and serum 25-hydroxyvitamin D in healthy young Canadian children. For our secondary objective we aimed to explore whether cow's milk consumption modifies this relationship. DESIGN/METHODS: Children attending one of seven pediatric or family medicine primary care practices were recruited during routine primary healthcare. For our primary analysis, a multiple linear regression model was developed to test the association between daily volume of non-dairy milk consumption and 25-hydroxyvitamin D, adjusted for age, gender, z-BMI, season, vitamin D supplementation, skin pigmentation, and daily outdoor play time. To explore whether cow's milk modifies this relationship, the interaction between non-dairy milk and cow's milk consumption was included in this model. RESULTS: A total of 2831 children were included in the analysis. Mean age was 2.9 years, 53% were male, 53% were taking a vitamin D containing supplement, 87% of children were consuming cow's milk and 13% of children consumed non-dairy milk daily. In the univariate analysis, each cup of non-dairy milk consumed per day was associated with a 2.3 nmol/L (P=0.005, 95% CI 1.0, 4.9) lower mean 25-hydroxyvitamin D concentration. Multiple linear regression, adjusted for clinically relevant covariates, revealed that each additional 250 ml cup of non-dairy milk was associated with a 3.8 nmol/L (95% CI 1.0 to 8.6; P=0.01) lower 25-hydroxyitmian D among children who drink cow's milk, and a non-significant increase in 25-hydroxyvitmain D of 0.3 nmol/L (95% CI −3.0 to 3.1; P=0.6) among children who do not drink cow's milk. CONCLUSIONS: Non-dairy milk consumption is associated with a lower 25-hydroxyvitamin D level in early childhood. This relationship appears to be modified by cow's milk consumption, suggesting that consumption of lower vitamin D containing non-dairy milk may be replacing consumption of higher vitamin D containing cow's milk.